Mussel adhesion is dictated by time-regulated secretion and molecular conformation of mussel adhesive proteins - Petrone, Luigi (2018)
Interfacial water constitutes a formidable barrier to strong surface bonding, hampering the development of water-resistant synthetic adhesives. Notwithstanding this obstacle, the Asian green mussel Perna viridis attaches firmly to underwater surfaces via a proteinaceous secretion (byssus). Extending beyond the currently known design principles of mussel adhesion, here we elucidate the precise time-regulated secretion of P. viridis mussel adhesive proteins. The vanguard 3,4-dihydroxy-L-phenylalanine (Dopa)-rich protein Pvfp-5 acts as an adhesive primer, overcoming repulsive hydration forces by displacing surface-bound water and generating strong surface adhesion. Using homology modelling and molecular dynamics simulations, we find that all mussel adhesive proteins are largely unordered, with Pvfp-5 adopting a disordered structure and elongated conformation whereby all Dopa residues reside on the protein surface. Time-regulated secretion and structural disorder of mussel adhesive proteins appear essential for optimizing extended nonspecific surface interactions and byssus’ assembly. Our findings reveal molecular-scale principles to help the development of wet-resistant adhesives.